2020
DOI: 10.1088/1361-6595/abbf95
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic theory of high-voltage low-pressure gas discharge with electron initiation on a cathode in a planar gap

Abstract: We report one-dimensional kinetic simulation of electron and ion transport and multiplication (based on the Boltzmann kinetic equations) in a self-consistent electric field after electron injection from the cathode. The 1D1V Boltzmann equations take into account the electron impact ionization, elastic electron scattering, and resonant ion recharging. The spatio-temporal evolution of the gas breakdown in a planar diode with a gap of 5 mm filled with nitrogen at pressure of 1 Pa, with applied voltage of 2.5 kV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…They can be used are also generated in tokamak-type setups, including ITER, and damage the internal components of the vacuum chamber [8][9][10][11]. In nanosecond gas discharges, REs are often generated in the prebreakdown stage [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. They can be measured directly with a collector or by measuring x-ray radiation [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…They can be used are also generated in tokamak-type setups, including ITER, and damage the internal components of the vacuum chamber [8][9][10][11]. In nanosecond gas discharges, REs are often generated in the prebreakdown stage [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. They can be measured directly with a collector or by measuring x-ray radiation [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The full kinetics of the collisionless expansion of the electron-ion plasma demonstrates the realistic velocities of the plasma jet and the energy spectrum of the ions in the flow. Of course, these conclusions do not exclude the influence of other mechanisms of ion acceleration in vacuum discharges, such as the 'potential hump' [13], 'electron wind' [6], or 'pressure gradient in fluid' [12]. We have shown that the only principles of physical kinetics give a good explanation of the observed facts.…”
Section: Discussionmentioning
confidence: 75%
“…There are many theoretical models of current transfer in vacuum and low-pressure discharges [6,13,14]. But most of these models describe plasma in terms of the fluid continuum approximation.…”
Section: Introductionmentioning
confidence: 99%
“…The charge of free electrons and ions is balanced, resulting in an overall electrical neutrality in the plasma. Within the Debye length, the Boltzmann kinetic equation serves as the fundamental equation for describing the distribution of plasma [12,13].…”
Section: Kinetic Equation For Electrons and Ionsmentioning
confidence: 99%